Review of the bee genus Eremaphanta Popov 1940 (Hymenoptera: Melittidae), with the description of a new species - Michez, Denis; Patiny, Séba S. (Zootaxa, 2006)
The small central Asian genus Eremephanta (Hymenoptera, Apoidea) is poorly known. We provide a catalogue of the eight species included in this genus and an update of the available diagnoses. One new species, Eremaphanta popovi sp. nov. and the male of E. fasciata Popov 1957 are described. A key to species is given and the species ranges are mapped and discussed.